If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -2 = 11x + 65 Reorder the terms: -2 + 2x = 11x + 65 Reorder the terms: -2 + 2x = 65 + 11x Solving -2 + 2x = 65 + 11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11x' to each side of the equation. -2 + 2x + -11x = 65 + 11x + -11x Combine like terms: 2x + -11x = -9x -2 + -9x = 65 + 11x + -11x Combine like terms: 11x + -11x = 0 -2 + -9x = 65 + 0 -2 + -9x = 65 Add '2' to each side of the equation. -2 + 2 + -9x = 65 + 2 Combine like terms: -2 + 2 = 0 0 + -9x = 65 + 2 -9x = 65 + 2 Combine like terms: 65 + 2 = 67 -9x = 67 Divide each side by '-9'. x = -7.444444444 Simplifying x = -7.444444444
| 8p+5q-1=0 | | y=-5x+15 | | 6+4x=39-x | | 6x+19=16+4 | | 6x+19=10x+4 | | 2(6-x)-11=5(3x+7) | | a=22b+c | | 10-x=21/4 | | (1/x)+(1/x+5)=9/100 | | 32445/75x^2+y^445 | | 4x+23=5x+17 | | 5x+29=10x+4 | | 3x-4x=x-2 | | 19x-2=0 | | lg(x+4)-lg(x-5)=1 | | 8c=4d | | E=x^3-5x^2+8x-4 | | 179=18 | | 3x-5y=73 | | 15x^4+15x^2+x^2+1= | | 8x^2-392=0 | | 5x^2-18x=-k | | 6x^5+36x= | | x^2-2304=0 | | 3(n+3)+8(n+6)= | | -5x-3.2=-3x+3.6 | | 4x+11=x+41 | | 127-7x=29X+23 | | -132-8=7x+18 | | 5X-9=149-37X | | ax+by+ay+bx=0 | | 2x+5=59-2x |